Optimization of Photoelastic Properties and Stress Relief of Small-Sized Polycarbonate Disks for Granular Material Photoelastic Tests - Hou, M.X.; Tang, M.X.; Hu, H.S. (Проблемы прочности, 2018)
The development of photoelastic tests was strongly enhanced by appearance of polycarbonate, hich turned out to be an excellent photoelastic material. In order to obtain small polycarbonate particles applicable for granular material photoelastic tests, small-diameter transparent cylindrical disks are cut from a polycarbonate plate preliminarily subjected to annealing, in order to provide stress relief. The plate-cutting and annealing regimes are optimized by the comprehensive analysis of mechanical and photoelastic properties of polycarbonate disks of various diameters and constant height of 5 mm. The resulting stress-strain photoelastic visualizations and material fringe patterns are analyzed, in order to verify the effectiveness of the proposed material processing and annealing regimes. Поликарбонат является оптимальным фотоупругим материалом для проведения механических испытаний методом фотоупругости. Для получения небольших частиц поликарбоната, применяемых при фотоупругих испытаниях гранулированного материала, из поликарбонатной пластины, предварительно подвергнутой отжигу для релаксации остаточных напряжений, вырезаются прозрачные цилиндрические диски малого диаметра. Режимы резки и отжига оптимизированы в результате анализа механических и фотоупругих свойств поликарбонатных дисков разного диаметра и постоянной высоты (5 мм). Анализ фотоупругих характеристик напряженно-деформированного состояния дисков и изохром подтвердил высокую эффективность предлагаемых режимов обработки и отжига для данного материала. Полікарбонат є оптимальним фотопружним матеріалом для проведення механічних випробувань методом фотопружності. Для отримання невеликих частинок полікарбонату, що використовуються при фотопружних випробуваннях гранульованого матер іалу, з полікарбонатної пластини, яку попереднью піддавали відпалу для релаксації залишкових напружень, вирізали прозорі циліндричні диски малого діаметра. Режими різання і відпалу оптимізовано в результаті аналізу механічних і фотопружних властивостей полікарбонатних дисків різного діаметра і постійної висоти (5 мм). Аналіз фотопружних характеристик напружено-деформованого стану дисків і ізохром підтвердив високу ефективність запропонованих режимів обробки і відпалу для даного матеріалу.